An Analysis of University Muhammadiyah Maumere Students’ English Speaking Skill - Saputra, Sahdan; Naro, Antonius M. K.; Putri, Velmi Maya (The Indonesian Institute of Science and Technology Research, 2025)
This research examines the English-speaking needs of students in the English Department at the University of Muhammadiyah Maumere. Collecting and analyzing data on needs helps the lecturer identify gaps between what has been done and what remains to be done. A needs analysis can help establish and implement language policy with significant implications. In this case, the analysis includes students' speaking levels and investigates students’ wants and needs in speaking English. The participants of this research were students majoring in English Education and Literature Study Program at the University of Muhammadiyah Maumere. This research used a qualitative research design. To find a comprehensive perception of each student, focus group discussion (FGD) is used. The results showed that the existing shortcomings found that student's level of English speaking skills was very low, and students often were afraid to speak because they were worried about making mistakes. Students need presents that students must learn to be brave to speak English at the level of daily communication. In addition, students’ desire found that students will use English speaking skills for job demands, they prefer pair or group projects in a teaching-learning process, and students prefer lecturers as facilitators and guides to improve speaking skills because they believe that poor speaking skills will have a negative impact on academic performance.